RECYCLING OF WASTE ELECTRICAL AND ELECTRONIC EQUIPMENT AS A STRATEGIC LINE TANGENTIAL OF CIRCULAR ECONOMY - Ruiz, Sara Nolasco; Castro, Hector Nuricumbo; Berra, Alejandro Vergara; Perez, Manuel Gonzalez (European Scientific Journal, ESJ, 2015)
Strategic planning allows the analysis and design of probable decisions in the environment of Organizations. Technological change has generated a large amount of electronic waste (E-Waste). In the health not only affects people but the entire World. The methodological application of the circular economy in Waste Electrical and Electronic Equipment (R2AE2) is done by defining efficiency indicators through linearization. A recursive decision feedback scheduling strategy for a system of efficient power generation. The competitive advantage of the circular economy through R2AE2 allows to obtain high revenues while providing adequate management in the Reduce, Reuse and Recycle (3R) of waste to avoid contaminating the environment. The proposed methodology aims to obtain similar results when applying EC strategy in South- Southeast of Mexico.